Magnesium in Combinatorial With Valproic Acid Suppressed the Proliferation and Migration of Human Bladder Cancer Cells - Li, Tianye; Yu, Yang; Shi, Hang; Cao, Yuhua; Liu, Xiangfu; Hao, Zhenzhen; Ren, Yuping; Qin, Gaowu; Huang, Yongye; Wang, Bing (Frontiers in Oncology, 2020)
Magnesium, the second most predominant intracellular cation, plays a crucial role in many physiological functions; magnesium-based biomaterials have been widely used in clinical application. In a variety of cancer types, the high intracellular concentration of magnesium contributes to cancer initiation and progression. Therefore, we initiated this study to investigate the likelihood of confounding magnesium with cancer therapy. In this study, the anti-tumor activity of magnesium and underlying mechanisms were assessed in bladder cancer both in vitro and in vivo. The results indicated that the proliferation of bladder cancer cells was inhibited by treatment with a high concentration of MgCl2 or MgSO4. The apoptosis, G0/G1 cell cycle arrest, autophagy, and ER stress were promoted following treatment with MgCl2. However, the migratory ability of MgCl2 treated cells was similar to that of control cells, as revealed by the trans-well assay. Besides, no significant difference was observed in the proportion of CD44 or CD133 positive cells between the control and MgCl2 treated cells. Thus, to improve the therapeutic effect of magnesium, VPA was used to treat cancer cells in combination with MgCl2. As expected, combination treatment with MgCl2 and VPA could markedly reduce proliferation, migration, and in vivo tumorigenicity of UC3 cells. Moreover, the Wnt signaling was down-regulated, and ERK signaling was activated in the cells treated with combination treatment. In conclusion, the accurate utilization of MgCl2 in targeting autophagy might be beneficial in cancer therapy. Although further studies are warranted, the combination treatment of MgCl2 with VPA is an effective strategy to improve the outcome of chemotherapy.